1995
DOI: 10.1007/bf00192378
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of the anxiolytics suriclone and alprazolam on cognitive information processing utilizing topographic mapping of event-related brain potentials (P300) in healthy subjects

Abstract: In a double-blind, placebo-controlled, cross-over study, acute effects of suriclone--a cyclopyrrolone derivative--were investigated by means of topographic mapping of event-related potentials (ERPs). Fifteen normal volunteers, aged 22-35 years, received randomized, oral single doses of placebo, 0.1 mg, 0.2 mg and 0.4 mg suriclone and 1 mg alprazolam as a reference compound. ERPs were investigated in an auditory oddball paradigm before and 3 h after intake of each drug. In addition to 17 EEG leads, vertical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…This decrease could be easily detected since the N100m remained relatively stable over time in the control conditions. The finding of a N100m dipole moment decrease by lorazepam is well in line with earlier EEG (Rockstroh et al, 1991;Semlitsch et al, 1995) and MEG (Sinton et al, 1986) studies, reporting an N100/N100m amplitude decrease by benzodiazepine intake. Interestingly, no N100 amplitude reduction was observed in the study by Nakagome et al (1998), who revealed a reduction of the MMN as an overnight effect of triazolam intake.…”
Section: Neuromagnetic Recordingssupporting
confidence: 91%
See 2 more Smart Citations
“…This decrease could be easily detected since the N100m remained relatively stable over time in the control conditions. The finding of a N100m dipole moment decrease by lorazepam is well in line with earlier EEG (Rockstroh et al, 1991;Semlitsch et al, 1995) and MEG (Sinton et al, 1986) studies, reporting an N100/N100m amplitude decrease by benzodiazepine intake. Interestingly, no N100 amplitude reduction was observed in the study by Nakagome et al (1998), who revealed a reduction of the MMN as an overnight effect of triazolam intake.…”
Section: Neuromagnetic Recordingssupporting
confidence: 91%
“…Summing up the current and earlier reported effects of benzodiazepines on event-related potentials (ERPs), midlatency ERPs (including P50) seem to be unaffected by benzodiazepines (Schwender et al, 1993), while the amplitudes of most if not all long-latency ERPs are decreased (Milligan et al, 1989;Nichols and Martin, 1993;Rockstroh et al, 1991;Semlitsch et al, 1995). Besides an enforced inhibition of neural circuits involved in the MMN generation by GABAergic interneurons, the observed reduction of the MMN could also stem from an attenuated efficacy in sensory information processing, as reflected by the decreased N100m (as a bottom-up process).…”
Section: Neuromagnetic Recordingsmentioning
confidence: 62%
See 1 more Smart Citation
“…These studies suggest detrimental effects of benzodiazepines on various stages of information processing, such as visual input [16][17][18], automatic feature registration [13,15], early stimulus discrimination [16], allocation of attention [13,15,18], usage of available processing capacity [15,16], context integration [13,14], central nervous system (CNS) excitability [17], cortical inhibition during memory consolidation [18], and recognition memory [19]. In those studies which adopted an auditory oddball task [20][21][22][23] as in this study, a significant reduction of P3 amplitude [20][21][22][23] was suggested, however, only one study suggested a reduction of N1 amplitude [20] and another study suggested a reduction in N2b amplitude [21] whereas no alteration was found in a third [22]. Prolongation of P3 latencies was reported in two studies [20,23] but not in two other studies [21,22], and only one study suggested a prolongation of N2b latencies.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies which adopted an auditory oddball task [20][21][22][23] as in this study, a significant reduction of P3 amplitude [20][21][22][23] was suggested, however, only one study suggested a reduction of N1 amplitude [20] and another study suggested a reduction in N2b amplitude [21] whereas no alteration was found in a third [22]. Prolongation of P3 latencies was reported in two studies [20,23] but not in two other studies [21,22], and only one study suggested a prolongation of N2b latencies. Urata et al [23] conducted ERP recordings at multiple time points, such as 1, 2, 4, 6 and 8 h after triazolam administration and found that P3 amplitude was significantly reduced and P3 latency was significantly prolonged at 2 and 4 h after administration.…”
Section: Discussionmentioning
confidence: 99%